The electrophysiologic properties of gonadotropin‐releasing hormone neurons. (22nd December 2021) - Constantin, Stephanie; Moenter, Suzanne M.; Piet, Richard
Abstract: For about two decades, recordings of identified gonadotropin‐releasing hormone (GnRH) neurons have provided a wealth of information on their properties. We describe areas of consensus and debate the intrinsic electrophysiologic properties of these cells, their response to fast synaptic and neuromodulatory input, Ca 2+ imaging correlates of action potential firing, and signaling pathways regulating these aspects. How steroid feedback and development change these properties, functions of GnRH neuron subcompartments and local networks, as revealed by chemo‐ and optogenetic approaches, are also considered. Abstract : For about two decades, recordings of identified gonadotropin‐releasing hormone (GnRH) neurons have provided a wealth of information on their properties. We describe areas of consensus and debate on the intrinsic electrophysiologic properties of these cells, their response to fast synaptic and neuromodulatory input, Ca 2+ imaging correlates of action potential firing, and signaling pathways regulating these aspects. How steroid feedback and development change these properties, functions of GnRH neuron subcompartments and local networks, as revealed by chemo‐ and optogenetic approaches, are also considered.